The impact of cultivar and irrigation on yield, leaf surface temperature and SPAD readings of chili pepper - Silva e Souza, Clarice; Agyemang Duah, Stella; Neményi, András; Pék, Zoltán; Helyes, Lajos (Acta Agraria Debreceniensis, 2020)
Paprika is an extremely popular and widespread plant species in Hungary. Chili peppers belongs to paprika and it can be consumed fresh or processed. The production of peppers began with the cultivation and control of some parameters for good results of paprika production. The aim of this article is to compare the water supply of four chili pepper hybrids ("Habanero", "Hetényi Parázs", "Unikal" and "Unijol") by means of investigation on open field and to examine how different temperatures and water stress factors influence the yield of chili peppers. The experiment area consisted of four different hybrids in three different irrigation treatments (control, deficit- and regular irrigation). The chlorophyll content was estimated with SPAD and the leaf surface temperature with Raytek MX4 TD. Our research concluded that deficit irrigation produced the highest yields for all cultivars and the lowest yields for the highest water supply.